Firm-Specific Strategic Advantages and Foreign Direct Investment Behavior of Firms: The Case of Japanese Semiconductor Firms - Kimura, Yui (Journal of International Business Studies, 1989)
We examine the effects of firm-specific strategic advantages on the FDI behavior of Japanese semiconductor firms. We investigate the strategic advantages necessary for undertaking FDI in this industry, and show that these advantages are systematically associated with the variation in FDI behavior. We identify technological innovation, a broad product line, and vertical linkages with down-stream businesses as sources of such strategic advantages. We also show that size of the firm influences its decision to go international.